Spin∞: an updated miniaturized spinning bioreactor design for the generation of human cerebral organoids from pluripotent stem cells. (October 2019) - Romero-Morales, Alejandra I.; O'Grady, Brian J.; Balotin, Kylie M.; Bellan, Leon M.; Lippmann, Ethan S.; Gama, Vivian
Graphical abstract: Abstract: Three-dimensional (3D) brain organoids derived from human pluripotent stem cells (hPSCs), including human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs), have become a powerful system to study early development events and to model human disease. Cerebral organoids are generally produced in static culture or in a culture vessel with active mixing, and the two most widely used systems for mixing are a large spinning flask and a miniaturized multi-well spinning bioreactor (also known as Spin Omega (SpinΩ)). The SpinΩ provides a system that is amenable to drug testing, has increased throughput and reproducibility, and utilizes less culture media. However, technical limitations of this system include poor stability of select components and an elevated risk of contamination due to the inability to sterilize the device preassembled. Here, we report a new design of the miniaturized bioreactor system, which we term Spinfinity (Spin∞) that overcomes these concerns to permit long-term experiments. This updated device is amenable to months-long (over 200 days) experiments without concern of unexpected malfunctions.